1994
DOI: 10.1007/bf00317326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth temperature and winter duration on leaf phenology of Erythronium japonicum, a forest spring geophyte

Abstract: The effects of growth temperature and winter duration on the leaf phenology of Erythronium japonicum were examined in two experiments. Bulbs wintered in the field were cultivated at 10 and 20° C and the bulbs were cultivated at 15° C after chilling treatment at 3° C for 60 and 120 days and without chilling in winter. The plants cultivated at 20° C showed significantly earlier leaf emergence, a more rapid rate of leaf extension and shorter leaf longevity than those cultivated at 10° C. The decrease in the leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 10 publications
7
24
0
Order By: Relevance
“…Experimental studies have shown that leaf senescence in spring ephemerals occurred under constant high light conditions (Risser and Cottam 1967;Yoshie and Fukuda 1994;Lapointe and Lerat 2006). This shows that leaf senescence is more or less independent of the light conditions.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Experimental studies have shown that leaf senescence in spring ephemerals occurred under constant high light conditions (Risser and Cottam 1967;Yoshie and Fukuda 1994;Lapointe and Lerat 2006). This shows that leaf senescence is more or less independent of the light conditions.…”
Section: Introductionmentioning
confidence: 91%
“…The most striking feature of the leaf death in spring ephemerals is that it is controlled by growth temperature and winter duration. Warm growth temperatures accelerate leaf senescence in E. japonicum (Yoshie and Fukuda 1994) and E. americanum (Lapointe and Lerat 2006). Longer chilling treatments accelerate leaf senescence in Erythronium albidum, Dicentra cucullaria (Risser and Cottam 1967) and E. japonicum (Yoshie and Fukuda 1994).…”
Section: Introductionmentioning
confidence: 98%
“…However, studies of the responses of spring ephemerals to different temperatures in the photosynthetically active phase of development are rare : the most consistent responses of these species to higher temperatures are earlier leaf emergence, more rapid rate of leaf extension, higher growth rate and shorter leaf longevity (Schemske et al, 1978 ;Yoshie & Fukuda, 1994).…”
Section: The Effect Of Temperaturementioning
confidence: 99%
“…The rate of respiration of P. sieboldii buds in this dormant period may be regarded as principally reflecting maintenance respiration. In general, the seasonal dormancy of spring ephemerals ends after the plants are exposed to low soil temperatures; growth activity is then resumed (Yoshie and Fukuda 1994;Lapointe 2001). The increased rate of respiration of P. sieboldii ramets after chilling (Fig.…”
Section: Discussionmentioning
confidence: 99%